Spondias tuberosa inner bark extract exert antidiabetic effects in streptozotocin-induced diabetic rats. (5th December 2018) - de Moura Barbosa, Humberto; Amaral, Dionísio; do Nascimento, Jailson Nunes; Machado, Dijanah Cota; de Sousa Araújo, Thiago Antônio; de Albuquerque, Ulysses Paulino; Guedes da Silva Almeida, Jackson Roberto; Rolim, Larissa Araújo; Lopes, Norberto Peporine; Gomes, Dayane Aparecida; Lira, Eduardo Carvalho
Abstract: Ethnopharmacological relevance: Diabetes mellitus (DM) is one of the most important medical emergencies of the 21st century. However, commercially available oral drugs with antidiabetic properties have been limited because of potential side effects, such as: hypoglycemia, weight gain, hepatic dysfunction and abdominal discomfort. As well as antidiabetic drugs, many types of medicinal herbal supplements are utilized as alternative treatments for DM and related comorbidities. Spondias tuberosa Arruda (Anacardiaceae), popularly known as "umbu", has been used in traditional medicine to treat a vast range of diseases, including DM, infections, digestive disorders, diarrhea and menstrual abnormalities. Aim of the study: This study evaluated the effect of the hydroethanolic extract of the inner stem bark of Spondias tuberosa (EEStb) in streptozotocin-induced diabetic rats. Materials and methods: Diabetes was induced in rats by a single injection of STZ (40 mg/kg i.p.). Diabetic rats were treated with 250 mg/kg or 500 mg/kg of the EEStb for 21 days. Water intake, urinary volume, body weight, as well as biochemical parameters, such as cholesterol total (TC), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), hepatic and muscle glycogen urea, alanine and aspartate aminotransferase, total protein, albumin, and glucose blood levels, were analyzed. We also determined the hepatic antioxidant state, as well as both of insulin and glucose tolerance. Results: The extract was evaluated by HPLC, and the major components of EESTb were identified (i.e. gallic acid and quercetin). The 500 mg/kg dosage of EEStb significantly decreased fasting blood glucose and post-prandial glucose. The EEStb also reduced urinary volume, food and water intake, as well as decreased body weight gain. Diabetic rats that received EEStb had a lower loss of muscle mass and white adipose tissue. Additionally, EEStb improved the urinary excretion of urea and glucose. The extract significantly decreased triglycerides, total cholesterol and VLDL in diabetic rats. However, no significant effect was observed on the levels of total and HDL cholesterol. EEStb treatment prevented hepatotoxic diabetic-induced, improved GSH:GSSG ratio, SOD and CAT activity as well as reduced nitrite and TBARs levels. Conclusions: Our results demonstrate that EEStb has antioxidant and hepatoprotective effects as well as improves insulin sensibility in diabetic rats. This indicates that S. tuberosa could be a potential resource for alternative therapies in the treatment of hyperglycemic conditions. These results also support the use of EEStb in ethnomedicine for the management of diabetes. Graphical abstract: